Don’t call me obasan ‘aunt’: Address practices towards aunts and conceptualisation of the kinship term obasan in contemporary Japanese - Yonezawa, Yoko (East Asian Pragmatics, 2024)
This study investigates the use of the kinship term obasan “aunt” as an address term in Japanese by analysing three types of data: metalinguistic discourse in online discussion; the most typical collocates for the term in a large corpus of Japanese websites; and the results of a survey of native speakers. The study demonstrates that address practices towards aunts appear to be changing. The most typically collocated adjectives and adjectival nouns with obasan as a term of reference in the corpus reveal an overwhelmingly negative conceptualisation of the term in contemporary contexts. The survey results show an increasing trend towards addressing aunts with their names and nicknames instead of obasan. The analysis shows an almost pejorative connotation of the fictive use of obasan, and this appears to interfere with its literal use as an address term towards actual kin, hence the decrease in its usage.